2021
DOI: 10.26451/abc.08.04.04.2021
|View full text |Cite
|
Sign up to set email alerts
|

The Welfare of Domestic Goats (Capra hircus) in a Zoo-Based Animal-Visitor Interaction Program

Abstract: We investigated whether the welfare of domestic goats in an animal-visitor interaction experience at a zoo was affected by the presence and behavior of visitors. We considered how the number of visitors in the goats’ habitat and visitor proximity to the goats impacted goat behavior. We also considered the goats’ behavior toward visitors, use of retreat space, and whether the visitors’ interaction style, specifically, how the visitors groomed the goats, was predictive of changes in the goats’ behavior. We condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…The behaviors observed suggest that at least some of the penguins found the bubble curtain enriching and indicate that a bubble curtain could be used to facilitate enriching experiences for some zoo-housed penguins. Importantly, this study highlights how animals have individualized responses to the care and enrichment provided, as has been seen in a wide range of species (e.g., goats (Capra hircus) [26]; chickens (Gallus gallus) [27]; squirrel monkeys (Saimiri sciureus) [28]; dolphins (Tursiops truncates) [29]; polar bears (Ursus maritimus) [30]; gorillas (Gorilla gorilla) [31]), as well as this colony of African penguins [14].…”
Section: Discussionmentioning
confidence: 67%
“…The behaviors observed suggest that at least some of the penguins found the bubble curtain enriching and indicate that a bubble curtain could be used to facilitate enriching experiences for some zoo-housed penguins. Importantly, this study highlights how animals have individualized responses to the care and enrichment provided, as has been seen in a wide range of species (e.g., goats (Capra hircus) [26]; chickens (Gallus gallus) [27]; squirrel monkeys (Saimiri sciureus) [28]; dolphins (Tursiops truncates) [29]; polar bears (Ursus maritimus) [30]; gorillas (Gorilla gorilla) [31]), as well as this colony of African penguins [14].…”
Section: Discussionmentioning
confidence: 67%
“…Observation and body temperature measurements are required when people participate in situations involving them. Ethically advancing the use of this species in zoos involves evaluating the animals' experiences, including human interaction and contact, during interactive activities [33][34][35]. This aligns with the current practice of AVIP and is of significant importance.…”
Section: Consideration Of Negative Behaviour Ethogram For Activity Pa...mentioning
confidence: 88%
“…given that some studies have found that visitor behavior may impact animal behavior independent of the number of visitors (Birke, 2002;Choo et al, 2011;Ramont et al, 2021b;Woods et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A final limitation is that we did not have information about the behavior or activity levels of visitors. We believe it would be valuable to explore these measures in future work, given that some studies have found that visitor behavior may impact animal behavior independent of the number of visitors (Birke, 2002 ; Choo et al, 2011 ; Ramont et al, 2021b ; Woods et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%